2021
DOI: 10.3390/pharmaceutics13081293
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan/Cyclodextrin Nanospheres for Levofloxacin Ocular Delivery

Abstract: Levofloxacin (LVF) is an antibacterial drug approved for the treatment of ocular infections. However, due to the low ocular bioavailability, high doses are needed, causing bacterial resistance. Polymeric nanospheres (NPs) loading antibiotic drugs represent the most promising approach to eradicate ocular infections and to treat pathogen resistance. In this study, we have developed chitosan NPs based on sulfobutyl-ether-β-cyclodextrin (CH/SBE-β-CD NPs) for ocular delivery of LVF. CH/SBE-β-CD NPs loading LVF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Ocular bacterial infections, including keratitis, conjunctivitis, blepharitis, endophthalmitis, dacryocystitis, and orbital cellulitis, are exciting targets to explore the extended role of chitosan as an active pharmaceutical ingredient. Common causes of infections comprise S. aureus, coagulase-negative Staphylococcus, P. aeruginosa, Streptococcus pneumonia, E. coli, and Serratia species [328]. However, successful localized therapy is highly dependent on the performance of the drug vehicle-delivery system.…”
Section: Ocular Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular bacterial infections, including keratitis, conjunctivitis, blepharitis, endophthalmitis, dacryocystitis, and orbital cellulitis, are exciting targets to explore the extended role of chitosan as an active pharmaceutical ingredient. Common causes of infections comprise S. aureus, coagulase-negative Staphylococcus, P. aeruginosa, Streptococcus pneumonia, E. coli, and Serratia species [328]. However, successful localized therapy is highly dependent on the performance of the drug vehicle-delivery system.…”
Section: Ocular Infectionsmentioning
confidence: 99%
“…Chitosan was often studied in combination with other pharmaceutical excipients; for example, chitosan/cyclodextrin nanospheres were evaluated in vitro for their potential to improve the delivery of levofloxacin, a third-generation tricyclic quinolone. Novel NPs exhibited 2-fold increased antibacterial activity against both Gram-positive and Gramnegative bacteria compared with the free drug [328]. Sustained release of levofloxacin was also achieved utilizing thermosensitive chitosan-based hydrogel targeting postoperative endophthalmitis.…”
Section: Ocular Infectionsmentioning
confidence: 99%
“…Such submicrocarriers have the potential to be used as a drug delivery system for the treatment of respiratory extracellular infection with P. aeruginosa and/or S. aureus [ 180 ]. CS NPs based on sulfobutyl-ether-β-CD with sizes 80 and 170 nm and a positive zeta potential loaded with levofloxacin (LEV) exhibited 2-fold higher antibacterial activity against both Gram-positive and Gram-negative bacteria, suggesting their suitability for ocular delivery of the antibiotic to treat ocular infections [ 181 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 99%
“…52 An enhanced in vitro antibacterial activity was reported by levofloxacin ocular nanospheres in another study. 53 Abruzzo et al deigned VAN-loaded nanoparticles for ocular delivery in 2021, that indicated antibacterial efficacy and enhanced diffusion through the mucus layer of the eye. 54…”
Section: In Vitro Release and Kineticsmentioning
confidence: 99%